Pengaruh Kualitas Pelayanan Cabin Crew Terhadap Kepuasan Pelanggan Garuda Indonesia: Studi Kasus: Di Bandar Udara Adi Soemarmo Pada Masa Pandemi Covid 19 - Auliyya Mujahidin Faruq As-syafiqi; Irwina Meilani (Yayasan Literasi Sains Indonesia, 2022)
Corona Virus or Covid-19 is a group of viruses that can infect the human respiratory system and its transmission is so fast, air transportation activities are very impactful with the presence of this virus. Quality of service is one of the strategies to attract consumers and has a very important role in meeting customer satisfaction. In a pandemic like today, airlines must pay more attention to services, especially in aircraft cabins so that passengers feel comfortable, safe, and clean. This research uses quantitative methods with primary data as well as secondary data. Quantitative research methods can be interpreted as research methods based on the philosophy of positivism, used to research on a particular population or sample. Based on the results of the study obtained the results of hypothesis testing using simple linear regression analysis in the SPSS 15.0 program. The significance value (Sig.) is 0.000 and the calculated T value is 9.525. Because of sig. 0.000 < 0.05 and the value of T calculates 9.5 25 > 1,966 T table, then in accordance with the basis of decision making in the T Test it can be concluded that Ho was rejected and Ha accepted which means that there is an influence between variable x on variable y or in other words The quality of cabin crew service affects grauda Indonesia Airline Customer Satisfaction at Adi Soemarmo International Airport.